Clinical and Epidemiological Characteristics of COVID-19 Patients in Chongqing China - Yang, Ao; Qiu, Qian; Kong, Xianghua; Sun, Yanyu; Chen, Tingying; Zuo, Yujie; Yuan, Danfeng; Dai, Wei; Zhou, Jihong; Peng, Anzhou (Frontiers in Public Health, 2020)
Objectives To study in-depth the clinical and epidemiological characteristics of pneumonia resulting from COVID-19 and provide evidence for effective public health decisions. Methods This was a retrospective, single-center research study. Participants were enrolled from patients presenting at the Chongqing Public Health Medical Treatment Center from Jan 24 to Feb 7, 2020, and were confirmed as having COVID-19. Results A total of 114 COVID-19 patients (99 mild, 4 severe, 11 critical) of which 56(56/114; 49.1%) were male, 58 (58/114; 50.9%) were female with a mean age of 46.05 years. Twenty nine (29/114; 25.44%) patients suffered from chronic diseases. Neutrophils counts in 23.7068% (27/114) of patients were abnormally low and abnormally high in 2221.9005% (24/114). Erythrocyte sedimentation rate and the C-reactive protein levels were abnormally elevated in 76.5% (62/81) and 62.9% (66/105) of patients, respectively. Creatine kinase isoenzymes (CK-MB), pro-brain natriuretic peptide (pro-BNP) and troponin levels were above the normal range in 7.10% (8/112), 66.7% (10/15) and 100% of patients, respectively. The percentage of patients in which the partial pressure of oxygen (PaO2)/fraction of inspired O2(FiO2) ratio exceeded 200 was 60%. A total of 91(91/114; 79.82%) patients displayed severe bilateral pneumonia, 52 (52/114; 45.61%) exhibited ground-glass opacity, and pulmonary consolidation was observed in 4 (3.51%) patients. Differences in shortness of breath, insomnia, inappetence, the procalcitonin (PCT) levels, FiO2 and PaO2/ FiO2 among the three groups were statistically significant (p＜0.05). Differences between the mild and severe groups was observed in neutrophil and lymphocyte counts, CD4 expression, and levels of C-reactive protein, alanine aminotransferase, aspartate aminotransferase and albumin (P＜0.05). Between the mild and critical groups, differences were observed in neutrophils, platelets, and CD4 expression (P＜0.05). A difference in C-reactive protein levels between severe and critical groups was also found (P＜0.05). Conclusions In the majority of cases no gender differences were observed and mostly the symptoms were mild. Evidence of efficient human‐to‐human virus transmission was found. The elderly with comorbidities were more prone to develop into severe or critical illness. Age and comorbidity may be risk factors for poor outcome.